2016
DOI: 10.3892/ol.2016.4394
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of recovery effect for sufentanil and remifentanil anesthesia with TCI in laparoscopic radical resection during colorectal cancer

Abstract: The aim of the present study was to compare the recovery of sufentanil and remifentanil anesthesia by target-controlled infusion (TCI) in elderly patients with laparoscopic-assisted radical resection of colorectal cancer. The effect of anesthesia on patient stress response and cellular immune function was also observed. Elderly patients (n=192) who underwent laparoscopic radical resection of colorectal cancer between July 2014 and October 2015 were randomly divided into the sufentanil and remifentanil groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Alfentanil decreases NK cell activity [ 52 ], and remifentanil has demonstrated suppression of NK cell activity and lymphocyte proliferation in a rat model [ 58 ]. A comparison of sufentanil and remifentanil using target-controlled infusion during laparoscopic colorectal cancer resection showed that cortisol and IL-6 increased more in the remifentanil group and that the proportion of T cell subsets decreased more in the sufentanil group [ 59 ].…”
Section: Effect Of Surgery On Immune Function and Tumor Metastasismentioning
confidence: 99%
“…Alfentanil decreases NK cell activity [ 52 ], and remifentanil has demonstrated suppression of NK cell activity and lymphocyte proliferation in a rat model [ 58 ]. A comparison of sufentanil and remifentanil using target-controlled infusion during laparoscopic colorectal cancer resection showed that cortisol and IL-6 increased more in the remifentanil group and that the proportion of T cell subsets decreased more in the sufentanil group [ 59 ].…”
Section: Effect Of Surgery On Immune Function and Tumor Metastasismentioning
confidence: 99%
“…40 Proper analgesic regimens can prevent both peripheral and central sensitization, thereby attenuating the postoperative amplification of pain sensation and consequently reducing postoperative stress and inflammatory response. 43,44 The levels of stress hormones and inflammatory mediators in our study were significantly lower in group T compared with group C at 1h in the PACU. This result is consistent with our findings of postoperative VAS pain scores.…”
Section: Discussionmentioning
confidence: 49%
“…Sufentanil increased the quantity of the Tregs to a greater degree than fentanyl when the culturing was conducted in vitro, while there was no significant difference between them in vivo [34]. In a clinical trial, total CD3 + , CD4 + , CD8 + cells and the ratio of CD4 + /CD8 + cells in the sufentanil group were significant higher than that in the remifentanil group [35]. There are few direct comparative studies which involved in the effects of sufentanil and morphine on immunity.…”
Section: Discussionmentioning
confidence: 99%